Modeling of Potential Distribution of Electrical Capacitance Tomography Sensor for Multiphase Flow Image - S. Sathiyamoorthy (Sensors & Transducers, 2007)
Electrical Capacitance Tomography (ECT) was used to develop image of various multi phase flow of gas-liquid-solid in a closed pipe. The principal difficulties to obtained real time image from ECT sensor are permittivity distribution across the plate and capacitance is nonlinear; the electric field is distorted by the material present and is also sensitive to measurement errors and noise. This work present a detailed description is given on method employed for image reconstruction from the capacitance measurements. The discretization and iterative algorithm is developed for improving the predictions with minimum error. The author analyzed eight electrodes square sensor ECT system with two-phase water-gas and solid-gas.